ASYMMETRIC AMINO-ACID SYNTHESIS - PREPARATION OF THE BETA-ANION DERIVED FROM ASPARTIC-ACID - Baldwin, J; Moloney, M; North, M (1989)
(S)-1-t-Butyl 4-methyl N-benzyloxycarbonylaspartate (5a), and (S)-1-t-butyl 4-allyl N-benzyloxycarbonylaspartate (5b) have been synthesized from (S)-aspartic acid (2), and can be readily alkylated and hydroxyalkylated at the β-carbon for asymmetric amino acid synthesis.